HAKIKAT BELAJAR ABAD KE-21 DALAM MENGINTEGRASIKAN KETERAMPILAN, PENGETAHUAN, DAN TEKNOLOGI SISWA SEKOLAH DASAR - Sofyan Iskandar; Dila Nurpadilah; Fitri Rohmatul Aulia; Isti, Istiba Hikmatul Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the essence of 21st-century learning in the context of integrating skills, knowledge, and technology in elementary school settings. This research employs a descriptive qualitative method using a literature review approach to analyze various relevant sources related to 21st-century education. The main focus is on how the learning process at the elementary level can accommodate the development of critical thinking, creativity, communication, and collaboration skills (4C), supported by the use of digital technology as a learning tool. The analysis reveals that 21st-century learning requires a paradigm shift from teacher-centered to student-centered learning, where teachers act as facilitators. The integration of technology plays a crucial role in encouraging students to actively seek, process, and apply information in real-life contexts. Therefore, a flexible, participatory, and future-oriented learning design is essential.